Current clinical practice in the screening and diagnosis of spatial neglect post-stroke: Findings from a multidisciplinary international survey. Issue 9 (21st October 2021) - Checketts, Matthew; Mancuso, Mauro; Fordell, Helena; Chen, Peii; Hreha, Kimberly; Eskes, Gail A; Vuilleumier, Patrik; Vail, Andy; Bowen, Audrey
ABSTRACT: Spatial neglect has profound implications for quality of life after stroke, yet we lack consensus for screening/diagnosing this heterogeneous syndrome. Our first step in a multi-stage research programme aimed to determine which neglect tests are used (within four categories: cognitive, functional, neurological and neuroimaging/neuromodulation), by which stroke clinicians, in which countries, and whether choice is by professional autonomy or institutional policy. 454 clinicians responded to an online survey: 12 professions (e.g., 39% were occupational therapists) from 33 countries (e.g., 38% from the UK). Multifactorial logistic regression suggested inter-professional differences but fewer differences between countries (Italy was an outlier). Cognitive tests were used by 82% (particularly by psychologists, cancellation and drawing were most popular); 80% used functional assessments (physiotherapists were most likely). 20% (mainly physicians, from Italy) used neuroimaging/ neuromodulation. Professionals largely reported clinical autonomy in their choices. Respondents agreed on the need for a combined approach to screening and further training. This study raises awareness of the translation gap between theory and practice. These findings lay an important foundation to subsequent collaborative action between clinicians, researchers and stroke survivors to reach consensus on screening and diagnostic measures. The immediate next step is a review of the measures' psychometric properties.